Development of numerical heat and mass transfer model for predicting total heat exchange performance in Energy Recovery Ventilator. Issue 5 (September 2019) - Sotokawa, H; Kameishi, K; Chung, J; Yoo, S; Ito, K
Abstract: An energy recovery ventilator (ERV) is a widely used equipment that can recover sensible and latent heat. To improve its performance, it is essential to understand the heat and moisture transfer mechanism in the ERV. Against this background, overarching objectives of this study are to develop mathematical/numerical models for predicting and clarifying the hygro-thermal (i.e. heat and moisture) transfer mechanism in the heat exchange element of the ERV in terms of (i) simplified model for sensitivity analysis, and (ii) comprehensive model to integrate hygro-thermal transfer equations with computational fluid dynamics (CFD) analysis. Toward this end, we conducted fundamental experiments to measure temperature, humidity, and enthalpy exchange efficiencies in the scale-down ERV unit model, and then, numerical analyses were conducted according to the experimental scenario. As results of this study, we confirmed the reasonable prediction accuracy of our proposed numerical models for predicting total heat exchange performances.